2015
DOI: 10.1177/230949901502300317
|View full text |Cite
|
Sign up to set email alerts
|

Early versus Late Surgery for Closed Ankle Fractures

Abstract: Patients with delayed surgery for ankle fracture had a longer postoperative length of hospital stay. Surgery should be performed within 24 hours of injury to minimise the length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
(18 reference statements)
2
20
2
Order By: Relevance
“…It has recently been reported that patients who have surgery for closed ankle fractures within 24 hours of injury have shorter length of stay than those operated on later [16]. Our data do not confirm this.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It has recently been reported that patients who have surgery for closed ankle fractures within 24 hours of injury have shorter length of stay than those operated on later [16]. Our data do not confirm this.…”
Section: Discussioncontrasting
confidence: 99%
“…The mean overall length of stay in our study of 1.72 days was considerably shorter than the mean of 4.38 days in the preliminary data that we had collected, and shorter than the mean 3.50 and 4.50 days of postoperative stay reported, respectively, by Lloyd et al [15] and Singh et al [16]. Consequently, the targeted reduction in length of stay of 1.5 days appeared to be unrealistic.…”
Section: Discussioncontrasting
confidence: 73%
“…Likewise, if ankle fractures were delayed more than 48 h, the length of stay in hospital and the cost increased significantly. Ankle fractures in individuals over 70 years of age have been shown a high rate of complications, such as infection and delayed wound healing, and they therefore need to be prioritised [ 52 ]. Pettersson et al [ 41 ] demonstrated that 20% of hip-fracture patients suffered a serious adverse event during their hospital stay and the risk of complications occurring increased linearly over time.…”
Section: Discussionmentioning
confidence: 99%
“…3 To prevent adverse side effects, urgent surgery is recommended in most cases of ankle fracture. Previous studies have reported higher rates of infection and longer hospital stays with delayed surgery compared with early surgery [4][5][6] .…”
Section: Introductionmentioning
confidence: 93%